2006
DOI: 10.1038/ni1307
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cells arise from monocytes in vivo

Abstract: Langerhans cells (LCs) are the only dendritic cells of the epidermis and constitute the first immunological barrier against pathogens and environmental insults. The factors regulating LC homeostasis remain elusive and the direct circulating LC precursor has not yet been identified in vivo. Here we report an absence of LCs in mice deficient in the receptor for colony-stimulating factor 1 (CSF-1) in steady-state conditions. Using bone marrow chimeric mice, we have established that CSF-1 receptor-deficient hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
659
3
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 624 publications
(707 citation statements)
references
References 53 publications
32
659
3
13
Order By: Relevance
“…Furthermore, we demonstrate differentiation of blood monocytes into lung DC under inflammation (Fig. 6), thus extending previous reports for skin and peritoneum (7)(8)(9). In addition, these monocyte-derived lung DC were capable of reconstituting CD4 ϩ T cell priming in an immunodeficient mouse model (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, we demonstrate differentiation of blood monocytes into lung DC under inflammation (Fig. 6), thus extending previous reports for skin and peritoneum (7)(8)(9). In addition, these monocyte-derived lung DC were capable of reconstituting CD4 ϩ T cell priming in an immunodeficient mouse model (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, in vivo studies also provide evidence that blood monocytes can act as precursors of M⌽ (1,5,6). More recent reports have shown that monocytes can under inflammatory conditions differentiate in vivo into conventional CD11c high DC (cDC) (7,8) and Langerhans cells (9). However, interestingly, blood monocytes seem not to contribute to the generation of splenic cDC (10 -12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, neither transfer of syngeneic BM cells in mice nor transfer of cells in parabiotic mouse models has supported this interpretation and a human patient with limb transplants was found to retain donor Langerhans cells for many years (reviewed in [16]). Subsequent studies have suggested that Langerhans cells survive by self-proliferation in normal tissue and are replaced by peripheral precursors after UV ablation [34]. More recently, with a milder inflammatory response, it appears that Langerhans cells may constitute a more independent cell population, able to selfrenew without input from peripheral sources [17] (unless a more absolute failure of the tissue-resident population occurs [34]).…”
Section: (Iii) Macrophage Reconstitution Of the Resolving Inflammatormentioning
confidence: 99%
“…Subsequent studies have suggested that Langerhans cells survive by self-proliferation in normal tissue and are replaced by peripheral precursors after UV ablation [34]. More recently, with a milder inflammatory response, it appears that Langerhans cells may constitute a more independent cell population, able to selfrenew without input from peripheral sources [17] (unless a more absolute failure of the tissue-resident population occurs [34]). A similar proposition has been made for microglia in the brain [18,19], leading to the suggestion that this mechanism of self-renewal by local proliferation may occur in tissues where leukocyte traffic is more restricted.…”
Section: (Iii) Macrophage Reconstitution Of the Resolving Inflammatormentioning
confidence: 99%